2019
DOI: 10.5465/amr.2017.0087
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Initiative Effectiveness: A Typological Theory of Unintended Consequences

Abstract: The purpose of diversity initiatives is to help groups that face disadvantage in society achieve better outcomes in organizations, but they do not necessarily work as intended. To advance understanding of the effects of diversity initiatives, I develop a typological theory of their unintended consequences. I propose that diversity initiatives produce four unintended consequence types: backfire (negative diversity goal progress), negative spillover (undesirable effects on outcomes other than diversity goal prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
340
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(356 citation statements)
references
References 116 publications
(242 reference statements)
11
340
1
4
Order By: Relevance
“…The opening quotes are a sample of the positive and negative responses we received to our privilege awareness activities. Vitriolic responses to privilege reminders may cause concern that asking people to reflect on their advantages makes them defensive or, even worse, backfires and increases resistance to egalitarianism (Dover, Kaiser, & Major, 2019;Knowles, Lowery, Chow, & Unzueta, 2014;Leslie, 2019). If negative reactions indicate changing attitudes in an unintended direction, then reminders of privilege may be ineffective at addressing inequality.…”
Section: Reminders Of Ingroup Privilege Often Threaten Identity But Rmentioning
confidence: 99%
“…The opening quotes are a sample of the positive and negative responses we received to our privilege awareness activities. Vitriolic responses to privilege reminders may cause concern that asking people to reflect on their advantages makes them defensive or, even worse, backfires and increases resistance to egalitarianism (Dover, Kaiser, & Major, 2019;Knowles, Lowery, Chow, & Unzueta, 2014;Leslie, 2019). If negative reactions indicate changing attitudes in an unintended direction, then reminders of privilege may be ineffective at addressing inequality.…”
Section: Reminders Of Ingroup Privilege Often Threaten Identity But Rmentioning
confidence: 99%
“…It is further differentiated from other forms of training, because it brings social identities (i.e., selfdefinitions tied to membership in social categories, such as race, sex, or ethnic group; Tajfel & Turner, 1979) to the forefront, potentially eliciting strong emotions from participants (Hanover & Cellar, 1998;Rynes & Rosen, 1995). Often, diversity training includes topics that may be uncomfortable for trainees, which may trigger personal trauma (Epstein, 1994), invoke deep emotions around one's own privilege (MacDonald, 1993), threaten valued identities or social status (Dover, Major, & Kaiser, 2016;Rawski, 2017), and increase unintended backfiring effects (Leslie, 2019;Rawski, 2017). These issues make diversity training unique from general diversity-related behaviors that occur outside of a training and development context and from general job-related training.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, organizational identification may motivate behaviors beyond the traditional training outcomes (e.g., reactions, learning, transfer, and results; Kirkpatrick, 1976;Holton, 1996). These outcomes are focused on meeting intended training objectives, but past research has indicated that training can lead to unintended outcomes too (Leslie, 2019;Rawski, 2017). Past empirical research on unintended training outcomes has mainly focused on negative backlash effects (Rawski, 2017;Tinkler, 2012) (Zhu, 2016).…”
Section: By Participating and Engaging In Diversity Training High Idmentioning
confidence: 99%
See 1 more Smart Citation
“…Sukurta autorių pagal Clark et al (2004) Vertėtų atkreipti dėmesį, kad nevisais atvejais socialinio verslo poveikis yra teigiamas. Kaip ir bet kurios kitos organizacijos privačiame ar viešajame sektoriuje, socialinis verslas gali sukurti ir neigiamus poveikius (Vanclay, 2002), dažniausiai dėl nenumatytų pasekmių (unintended consequences), nors misija išlieka kilni (Leslie, 2019;Wegrich, 2019). Nors mokslinėje literatūroje neigiami poveikiai nėra nagrinėjami socialinio verslo veiklos kontekste, tačiau tokių pavyzdžių praktikoje aptinkama.…”
Section: Socialinio Verslo Poveikių Vertinimo Prieigosunclassified